Implementation Of Religious Moderation In Economic Development and Village Community Empowerment - Munthe, Faisal Amir (Lembaga Penelitian dan Pengabdian Kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2025)
This research discusses the strategic role of religious moderation in supporting populist economic development and village community empowerment. Religious moderation, which emphasizes the values of balance, tolerance, and justice, contributes to creating social cohesion which is an important foundation for inclusive and sustainable village development. Through a qualitative approach with a literature study method, this research examines scientific literature and policy documents to understand the relationship between moderate religious values and village socio-economic dynamics. The results show that the implementation of religious moderation encourages collective participation, strengthens social capital, and facilitates cross-group cooperation in economic activities such as cooperatives, MSMEs, and BUMDes. Case studies in various villages show that religious forums, mutual cooperation activities, and education on the value of tolerance can increase solidarity and local economic productivity. Thus, religious moderation is not only relevant as a theological concept, but also as a practical approach to strengthen the capacity of village communities. This research recommends mainstreaming religious moderation in village development policies through collaboration between the government, religious leaders, and civil society to create peaceful, prosperous, and independent villages.